John logie baird - Goldsmith, Mike (Hodder Wayland London, 2003)
As well as telling the story of Baird's life from his childhood in Scotland to his international fame as 'the Television Man', this book looks at the impact of his invention in terms of its importance in world history. It explains the science behind the invention of the television with diagrams, and quotes from Baird and his contemporaries.